HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN TEKANAN DARAH SISTOLIK DI PUSKESMAS RAWAT INAP SIMPUR BANDAR LAMPUNG TAHUN 2022 - Ika Artini; Sandhy Arya Pratama; Firhat Esfandiari; Richard Bartolomeus Alton (CV. Jasa Sukses Abadi, 2022)
Hypertension is a condition when a person has systolic blood pressure 140 mmHg and/or diastolic blood pressure 90 mmHg, on repeated examinations. The main blood pressure measurement that is the basis for determining the diagnosis of hypertension is diastolic blood pressure measurement. Hypertension with obesity is still very common. The prevalence of hypertension accompanied by obesity is also still increasing today. According to several studies, obesity and hypertension have a significant relationship. There are several explanations that patients who have a BMI with obesity will have a risk of 1.64 times to suffer from hypertension compared to BMI. Research Objectives To determine the correlation between body mass index degrees with blood pressure at public health center of Simpur in Bandar Lampung 2021. This type of research is quantitative research. With the analytical survey method using cross sectional design, through questionnaires given online to respondents who meet the inclusion criteria. Sample obtained was 97 respondents. The degree of blood pressure with the highest number of respondents was the degree of hypertension level 2 systolic >160 as many as 51 people (52.6%), the most age group were adult patients with an age range of 20-59 years as many as 66 people (68%), the degree of body mass index The highest number was obesity level 2 30 as many as 61 people (62.9%), the relationship between the degree of body mass index and the degree of blood pressure was mostly obesity level 2 with blood pressure of hypertension level 2 as many as 35 people (32.1%). Spearman test obtained p = 0.000 (p <0.05). There is a relationship between the degree of body mass index with the degree of blood pressure with the results of the Spearman test obtained p = 0.000 (p <0.05).